2000
DOI: 10.1007/s004240000261
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular pH in isolated rat renal papillary thin limbs of Henle's loop

Abstract: Intracellular pH (pHi) was measured in isolated, nonperfused and perfused rat papillary thin limbs of Henle's loops in N-2-hydroxyethylpiperazine-N'-2-ethansulfonic acid (HEPES)- or HEPES/bicarbonate-buffered medium at pH 7.4 using the pH-sensitive fluorescent dye 2',7'-bis(2-carboxyethyl)-5,6-carboxyfluorescein (BCECF). Resting pHi was about 6.7 in descending thin limbs (DTL) and about 6.9 in ascending thin limbs (ATL), even with a medium pH of 7.4. These values appeared to reflect the acid pH of the blood in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…This acid pH in the vasa recta reflects an increase in pCO 2 and a decrease in [HCO 3 -] compared to the systemic blood [31]. We also found that the resting pH i of the thin limbs from this inner medullary region is significantly acid, even when these thin limbs are maintained in a standard buffer at pH 7.4 in vitro [18]. In addition, the resting pH i of the descending thin limbs (DTL) is significantly more acid than that of the ascending thin limbs (ATL) [18].…”
Section: Introductionmentioning
confidence: 66%
See 4 more Smart Citations
“…This acid pH in the vasa recta reflects an increase in pCO 2 and a decrease in [HCO 3 -] compared to the systemic blood [31]. We also found that the resting pH i of the thin limbs from this inner medullary region is significantly acid, even when these thin limbs are maintained in a standard buffer at pH 7.4 in vitro [18]. In addition, the resting pH i of the descending thin limbs (DTL) is significantly more acid than that of the ascending thin limbs (ATL) [18].…”
Section: Introductionmentioning
confidence: 66%
“…We also found that the resting pH i of the thin limbs from this inner medullary region is significantly acid, even when these thin limbs are maintained in a standard buffer at pH 7.4 in vitro [18]. In addition, the resting pH i of the descending thin limbs (DTL) is significantly more acid than that of the ascending thin limbs (ATL) [18]. We speculated that this difference between the limbs might reflect a cellular memory of the pH of the surrounding vasa recta blood in vivo [18].…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations